The Joola civilization and the management of mangroves in Lower Casamance, Senegal - Claudette Soumbane Diatta; Malick Diouf; Amadou Abdoul Sow; Charlotte Karibuhoye (Revue d'ethnoécologie)
The mangrove ecosystem is one of the most productive in Casamance and the most important biomes in Senegal. This threatened ecosystem is found on the banks of Casamance river and along its tributaries, known as the bolong or inlets. The importance of the mangrove ecosystem results from its biodiversity and its ecological, economic and socio-cultural in particular functions ritual places, totem cockpit, etc. The Lower Casamance mangroves are the site of diverse traditional representations and activities of the Joola society, including prohibitions on the cutting of mangroves and seasonal restrictions on the harvesting of oysters in restricted access. We conducted research designed to understand the practices associated with the use of mangroves by the Joola society. The methodology we used is a combination of qualitative and quantitative approaches. Semi-structured informal and individual interviews, as well as field observations were carried out. The results of our research show that mangroves are considered sacred by the Joola and that the practices they conduct in these areas are governed by very strict and traditional rules. These practices are animated by various representations that crystallize their behaviors in totems, taboos, rituals and the sacredness of natural spaces. However, with the adoption of monotheistic religions notably Islam and Christianity, certain prohibitions and beliefs that have preserved these spaces are disappearing and that mangroves are deteriorating. Therefore, traditional methods of in situ conservation must be preserved in order to ensure the protection of mangrove ecosystems. This article highlights the importance of Joola customs and practices and reviews traditional methods that have favored the conservation of parts of the mangrove.